2017
DOI: 10.1017/s0954579417000426
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions in preventing disorganized attachment: A meta-analysis

Abstract: Disorganized attachment is associated with a host of negative developmental outcomes, leading to a growing interest in preventative interventions targeting the attachment relationship in infancy. The objective of this meta-analysis was to assess the effectiveness of interventions that aimed to prevent or reduce rates of disorganization among children at risk. We performed a literature search using PsycINFO, MEDLINE, and ProQuest databases for studies published between January 1989 and August 2016. All 16 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 55 publications
0
40
0
2
Order By: Relevance
“…In a systematic review and meta‐analysis of sixteen studies, Facompré et al . () found that a range of systemic interventions were effective in reducing rates of disorganized child‐parent attachment in at‐risk families. Interventions covered in this meta‐analysis and in a narrative review by Berlin et al .…”
Section: Problems Of Infancymentioning
confidence: 99%
“…In a systematic review and meta‐analysis of sixteen studies, Facompré et al . () found that a range of systemic interventions were effective in reducing rates of disorganized child‐parent attachment in at‐risk families. Interventions covered in this meta‐analysis and in a narrative review by Berlin et al .…”
Section: Problems Of Infancymentioning
confidence: 99%
“…The concept of disorganized infant attachment was initially proposed to account for conflicted, disoriented, or fearful behavior shown by infants toward their caregiver in a laboratory setting (Main & Solomon, 1986, 1990). This work has led to an array of empirical research that has tested key assumptions about the causes and implications of disorganized attachment (Madigan et al, 2006; van IJzendoorn, 1995) and now provides the evidence base for intervention programs (see Facompré, Bernard, & Waters, 2017; Steele & Steele, in press). There has also been appeal to the disorganized attachment classification in the context of custodial placements and child welfare assessments.…”
Section: Introductionmentioning
confidence: 99%
“…These supportive interventions have all demonstrated – in randomized controlled trials – that the caregiving conditions contributing to (or maintaining) disorganized attachment can be changed even among very high-risk families (for meta-analytic results, see Facompré et al, 2017). Additionally, they have helped us understand important therapeutic mechanisms that can be used by clinicians and child welfare practitioners outside of manualized interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding attachment theory assists paediatricians in understanding family dynamics and allows practical interventions that allow the creation of nurturing, safe and stable relationships between children and parents. This, in turn, can break intergenerational cycles of trauma and lead to diminished numbers of children with disorganised attachment styles …”
Section: Discussionmentioning
confidence: 99%